FRAMING ANALYSIS ON NEWS OF ISLAMIC STATE OF IRAQ AND SYIRIA IN WASPADA DAILY NEWS - Abdul Rasyid; Syukur Kholil; Suwardi Lubis (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to get the intent and purpose of news about ISIS in Haria Waspada. This study uses a descriptive qualitative approach in which the researcher describes the data that exist in Waspada by using Framing analysis, namely analysis with emphasis on; 1 Scheme, 2 Script, 3 Thematics, and 4 Rhetoric. The data in this study focuses on ISIS news in the Daily News of Waspada, in this study focused on 3 news which is phenomenal related to ISIS. The research results show that: 1. In the scheme, all elements of the Daily Alert report have fulfilled the sheme requirements, wherein there must be a Headline, Lead, Background of Information, Statement and Closing. 2 In Script, This Coverage has used a good script model which includes the script elements, they are; What, Who, Where, When, Why and How. 3 in thematics, the daily news of Waspada has fulfilled its elements, they are; Paragraph and Proportion. 4 while in the Rhetoric element, the ISIS report on the Daily news of Waspada has included all elements of Rhetoric, they are; Words, Idiom Picture, and Graphic. In conclusion, Framing Analysis of news related to ISIS in the Daily News of waspada can be a scientific reference because it has fulfilled all the elements contained in the Framing analysis. Keywords: Framing Analysis, ISIS, Waspada Daily News